ANALISIS TINGKAT KEPUASAN PELANGGAN TERHADAP PELAYANAN BIRO PERJALANAN WISATA GAMAWISATA - , MARLINA DWI ANDARI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The economy is moving forward to make their lifestyle change, one thing that they did was to travel or just to travel from place of origin to go to many different destinations. Any travel agent that helps in getting tickets grew in number as in the Gama Wisata travel agency that sells airline tickets and train tickets. In this case the measurement required level of satisfaction with the services already provided Gama Wisata and Standard Operating Procedures know who owned Gama Wisata. This study aims to determine the Standard Operating Procedure Gama Wisata and to determine customer satisfaction. This study was conducted for three months and the means used to obtain the data is by observation, questionnaires and literature. Then the data was obtained were analyzed using descriptive statistical analysis. The services provided Gama Wisata travel agency has included successful because of the research can be known that the customer is satisfied with the service and assess Gama Wisata service with good value. Standard Operating Procedure owned Gama Wisata was applied by frontliner Gama Wisata.